Dowel-inlay a new treatment approach to traumatic root fracture - R G Sunil Reddy (Wolters Kluwer Medknow Publications, 2010)
Tooth trauma has been and continues to be a common occurrence that every dental professional must be prepared to assess and treat when necessary. Tooth trauma and its management loom as a major challenge to the dental practitioner. Transverse root fractures occur most commonly in the maxillary teeth. This case report describes a new technique for the management of transverse root fractures in zone 2 with dowel inlay. This enables the utilization of the fractured fragment crown for stabilizing a transverse root fracture in zone 2, in a simple, economical, and minimally invasive manner. It can save considerable time over other alternative treatment options available for the treatment of trauma zone 2 fractures. Both clinical and radiographic follow-up have shown a stable condition, without any probing defects, ongoing root resorption or periapical pathosis.